Perceptions of the body and sacred space in late antiquity and Byzantium - Bogdanović, Jelena (Routledge, Taylor & Francis Group, 2018)
Images of invisible beauty in the aesthetic cosmology of Dionysius the Areopagite / Filip Ivanović -- Monumental icons and their bodies in early Christian Rome and Byzantium / Maria Lidova -- Imperial bodies and sacred space? imperial family images between monumental decoration and space definition in late antiquity and Byzantium / Maria Cristina Carile -- The influence of icons on the perception of living holy persons / Katherine Marsengill -- Delivering the sacred : representing translatio on the Trier Ivory / Ljubomir Milanovic -- Bodies in motion : visualizing trinitarian space in the Albenga Baptistery / Nathan S. Dennis -- A mobile dialogue of an immobile saint : St. Symeon the Younger, divine liturgy, and the architectural setting / Ayşe Belgin-Henry -- Framing glorious spaces in the Monastery of Hosios Loukas / Jelena Bogdanović -- Conclusions. Iconic perception and noetic contemplation of the sacred / Jelena Bogdanović with Katherine Marsengill